Nurses' Role in Taking Care of Gestational Diabetes Mellitus Patients: A Qualitative Study - Tri Ismu Pujiyanto; Indah Wulaningsih (Universitas Airlangga, 2021)
Introduction: Gestational Diabetes Mellitus (GDM) is becoming one of the major public health problems. It is important to screen the GDM and for the case to be managed by nurses. Nurses are needed to care for pregnant women with GDM, and the work experience of nurses is directly related to the assistance and quality of care provided. However, nurses face some barriers in understanding the GDM and providing good management thereof. This study explored the experiences of nurses of caring for GDM patients. Methods: This study was a phenomenological approach qualitative research. Participants were 10 nurses who provide care for pregnant women with GDM selected by purposive sampling technique with sampling criteria. Data analysis used the Colaizzi method. Results: There were five categories, e.g. empathy, inspiration to find ways to treat patients very well, feeling of ambivalence, self-preservation to develop potential, and the impact on the nurses of caring for GDM. Conclusion: Sustaining the nursing workforce and improving their working experiences are essential to meet the care needs of pregnant women with GDM. Nurses should understand to promote empathy, and there is a need to improve the job satisfaction and morale of nurses. At the institutional level, policy makers should make efforts to improve the nursing clinical practice environment, increase the nursing management role, the maternity nursing education and training, achieve a proper skill mix of the health workforce, and, overall, attract, prepare and sustain nurses regarding caring for pregnant women with high risk GDM.